(untitled) (Physical Education, Health and Social Sciences, 2025)
The integration of Artificial intelligence in healthcare setting has the potential to transform the delivery of patient care. However, the success of AI adoption depends on the perception and attitudes of nurse managers, who play a crucial role in implementing and managing healthcare technologies. Such developments will only serve to strengthen the place of AI in the provision of health care services, as well as in the management of patients The healthcare industry is experiencing a significant shift towards digital transformation, with AI being a key driver of this change. This study employed a cross-sectional design, using convenience sampling and questionnaire was designed on Likert scale. Data collected was systematically organized and analyzed using SPSS and Excel. As a result, this research supportss the alternate hypothesis and reject the null hypothesis. AI is recognized as having the potential to revolutionaries’ healthcare, by enhancing the quality of care delivered to patients, streamlining many backend tasks, as well as supporting medical decisions. Establish elaborate training programs tailored towards teaching nurse managers all that they need to know about the AI systems to use and how to use them to their advantage. Skills training should involve demonstration and ethics, agendas and cases on success stories of Artificial Intelligence tools.